1997
DOI: 10.1099/0022-1317-78-9-2247
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetic diversity and phylogenetic relationship of Italian isolates of feline immunodeficiency virus indicates a high prevalence and heterogeneity of subtype B.

Abstract: The genetic diversity of 32 Italian isolates of feline immunodeficiency virus (FIV) was studied. Isolates were obtained from domestic cats living in different areas. Sequence data were obtained from a 308 bp fragment of the p25 region of the gag gene. Phylogenetic relationships among these sequences and previously published sequences were determined. All the Italian isolates could be assigned to subtype B ; however, four isolates formed two separate clusters and may represent genetic out-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
47
1
3

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 31 publications
3
47
1
3
Order By: Relevance
“…Encouraging results have indicated that it is possible to protect cats against challenge with primary FIV isolates, depending on their regional distribution. By vaccinating cats with a whole inactivated vaccine based on the subtype B Pisa M2 strain, cats were protected from natural challenge with subtype B isolates of FIV (Pistello et al, 1997). It has been suggested that subtype B isolates may be more ancient and, accordingly, more host-adapted (Bachmann et al, 1997), hence they may be more readily neutralizable by the host humoral response.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging results have indicated that it is possible to protect cats against challenge with primary FIV isolates, depending on their regional distribution. By vaccinating cats with a whole inactivated vaccine based on the subtype B Pisa M2 strain, cats were protected from natural challenge with subtype B isolates of FIV (Pistello et al, 1997). It has been suggested that subtype B isolates may be more ancient and, accordingly, more host-adapted (Bachmann et al, 1997), hence they may be more readily neutralizable by the host humoral response.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to HIV-1, FIV isolates have been grouped into different clades or subtypes (designated A to D) with different geographic distributions (2). For example, clade A FIV is prevalent in northern Europe and the United States, while clade B FIV is highly predominant in Italy (26).…”
mentioning
confidence: 99%
“…A number of FIV strains have been identified throughout the world, and their corresponding genomes have been partially sequenced (1,5,6,10,13,15,18,19,22,27,32). Studies developed on the basis of the nucleotide sequences from the envelope gene separated FIV strains into five distinct phylogenetic subtypes designated A to E (1, 2, 10, 13,22,27).…”
mentioning
confidence: 99%
“…Studies developed on the basis of the nucleotide sequences from the envelope gene separated FIV strains into five distinct phylogenetic subtypes designated A to E (1, 2, 10, 13,22,27). Although geographic isolation could be a major factor in the evolution of FIV, individual subtypes are found in more than one part of the world (1,2,5,13,19,27).…”
mentioning
confidence: 99%